Retinal Changes After Posterior Cerebral Artery Infarctions Display Different Patterns of the Nasal und Temporal Sector in a Case Series - Lee, John-Ih; Boerker, Laura; Gemerzki, Lena; Harmel, Jens; Guthoff, Rainer; Aktas, Orhan; Gliem, Michael; Jander, Sebastian; Hartung, Hans-Peter; Albrecht, Philipp (Frontiers in Neurology, 2020)
Background: Visual field defects are a common and disabling consequence of stroke and a negative prognostic factor of patient's quality of life. They result from lesions in different parts of the visual system, most commonly the visual cortex and optic radiation. An important pathophysiological mechanism is transsynaptic retrograde degeneration (TRD). Methods: In a case series 21 patients with posterior cerebral artery (PCA) territory infarctions were analyzed by spectral-domain optical coherence tomography (SD-OCT) and multifocal visual evoked potentials (mfVEPs) cross-sectionally and longitudinally for up to 6 months. In OCT, symptomatic affected nasal and temporal sectors and corresponding visual fields in mfVEPs were compared to the contralateral side. Results: SD-OCT revealed a significant reduction (−2.92 ±2.53 μm, mean ± SD) of the symptomatic nasal macular retinal nerve fiber layer (RNFL) thickness and of the symptomatic temporal peripapillary RNFL after 6 months compared to baseline whereas the symptomatic temporal macular quadrant already showed a significantly thinner RNFL at baseline. The mfVEP first peak latency at baseline was significantly different (nasal visual field +11.69 ±11.17 ms, mean ± SD; temporal visual field +16.63 ±7.97 ms, mean ± SD) on the symptomatic compared to the asymptomatic field. The nasal visual fields partly recovered in amplitude and first peak latency of mfVEPs over the following 6 months compared to baseline. Conclusion: The dynamics of OCT and mfVEP outcomes for degeneration and recovery after PCA infarction differ between the nasal and temporal retinal sector. We postulate that retinal sectors may differ in their temporal pattern of TRD over time after retrogeniculate cerebral infarction.